The use of the kinesio taping in the extensor musculature of the knee after surgery of anterior cruciate ligament: case report. - Paulino, Flávia Maria Pinheiro; Vasconcelos, Thiago Brasileiro de; Pereira, Érica da Rocha; Farias, Maria do Socorro Quintino; Bastos, Vasco Pinheiro Diógenes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The Kinesio Taping method (KT) was created by the Japanese chiropractor Kenso Kase in the 70s. He was trying to develop a tape which could help the normal function of the muscle tissue in order to give an external support without cause limitations to these tissues. Objectives: To evaluate the strength of extensor musculature of patients’ knees in the post-operatory of the anterior cruciate ligament (ACL) and compare the strength, power and resistance of the extensor musculature of the knee with and without the use of the tapes of the KT method. Method: The studying of the kind of the reported case, where it was applied the KT tape on the extensor musculature of a patient’s knee who was undergone corrective surgery of ACL, it was used the Biodex SYSTME 3 PRO. Results: It was verified that in the first exam the left femoral quadriceps presented the deficit of strength, power and resistance related to the right one. In the third exam it was applied the KT tape and there was a decrease of the deficits of strength and power and an increase of the deficit of resistance. Conclusion: The use of the KT tape potentiates the gain of the strength and power of the weakened musculature and increase the values of the deficit of the muscle resistance and it can be a auxiliary resource in the physiotherapic treatment.